Arabic validation of the “Mental Health Knowledge Schedule” and the “Reported and Intended Behavior Scale” - Ben Amor, Maryem; Zgueb, Yosra; Bouguira, Emna; Metsahel, Amani; Aissa, Amina; Thonicroft, Graham; Ouali, Uta (Frontiers in Psychiatry, 2023)
Objectives: Mental illness affects one in eight people in the world according to the WHO. It is a leading cause of morbidity and a major public health problem. Stigma harms the quality of life of people with mental illness. This study aimed at validating the Arabic version of the Mental Health Knowledge Schedule (MAKS) and the Reported and Intended Behaviour Scale (RIBS) in a sample of Tunisian students and determining socio-demographic and clinical factors correlated with stigma.Methods: This cross-sectional study was conducted on 2501 Tunisian students who filled in the MAKS, the RIBS, and a sociodemographic and clinical questionnaire. The validation of the questionnaires in Arabic was carried out using the validity criteria: face and content validity, reliability, and construct validity. Next, the associations between stigma and sample characteristics have been studied using multivariate linear regression.Results: Face and content validity of the measures MAKS and RIBS were satisfactory, with adequate internal consistency. There were significant positive correlations between the items and scales, and test-retest reliability was excellent. The internal validity showed that the items were well-aligned with the intended factors, and the external validity revealed a significant positive relationship between the MAKS and RIBS. Besides, gender, the field of study, psychiatric history, and contact with someone with a mental illness were all contributing factors to mental illness stigma. Additionally, men performed better than women in terms of behavior toward people with mental illness, while women had a greater level of knowledge about mental health.The Arabic versions of the MAKS and RIBS have appropriate psychometric properties, making them effective tools for evaluating mental illness stigma. With multiple factors contributing to this issue, these instruments can help focus anti-stigma efforts and promote a more inclusive society.